ANTIBODIES SPECIFIC TO ESTRADIOL AND GENES POLYMORPHISMS OF DNA-REPAIRING ENZYMES IN BREAST CANCER PATIENTS - Andrey N. Glushkov; Elena G. Polenok; Varvara I. Minina; Anastasia V. Torgunakova; Margarita V. Katanakhova; Mikhail V. Kostyanko; Alexander V. Antonov; Pavel V. Bayramov; Gleb I. Ivanovich (Медицинская иммунология, 2019)
The aim of this study - to investigate the associations of blood serum idiotypic and antiidiotypic antibodies specific to estradiol (IgA1-E2 and IgG2-E2) with genes polymorphisms of DNA-repairing enzymes in breast cancer patients (BCP) according to Ki-67 positive cells in tumor.  Idiotypic and antiidiotypic antibodies in the blood serum of BCP (360 at the I stage and 376 at the II–IV stages) were measured by enzyme-linked immunosorbent assay. Prevalence of hOGG1 (rs1052133), XRCC1 (rs25489), XPD (rs13181), APEX1 (rs1130409) were determined by allele-specific polymerase chain reaction. High levels of Ki-67 positive cells in tumors (>30%) were revealed in 47.9% and 58.9% BCP II–IV stages with low and high IgA1-E2 levels (p = 0.035); in 61.2% and 46.9% BCP II–IV stages with low and high IgG2-E2 levels (p = 0.001). High Ki-67 tumor levels were found in 55.6% BCP with low levels both IgA1-E2 and IgG2-E2; in 67.6% BCP with high IgA1-E2 levels combined with low IgG2-E2 levels; in 43.2% BCP with low IgA1-E2 levels combined with high IgG2-E2 levels; in 52.2% BCP with high both IgA1-E2 and IgG2-E2 levels. So IgG2-E2 inhibited the tumor proliferation but IgA1-E2 blocked this effect. There were no revealed any associations of hOGG1, XRCC1, XPD, APEX1 genes polymorphisms with Ki-67 positive cells tumors levels. High IgA1-E2 levels were found in 39.9% BCP with CC hOGG1 genotype and in 47.8% BCP with CG hOGG1 genotype (p = 0.049). High IgG2-E2 levels were revealed in 65.3% and 53.7% correspondingly (p = 0.003). High IgG2-E2 levels in combination with low IgA1-E2 levels were revealed in 40.6% BCP with CC hOGG1 and in 27.2 % BCP with CG hOGG1 genotypes. The other combinations of low and high levels of IgA1-E2 and IgG2-E2 were found more frequent in CG hOGG1 BCP. The differences between CC and CG hOGG1 BCP according to prevalence of anti-proliferative and pro-proliferative immunological phenotypes were statistically significant (p = 0.003).It was shown for the first time that the formation of antibodies that modulate the proliferative activity of a tumor may be associated with variants in the genes for DNA repair enzymes. In particular, the formation of idiotypic and antiidiotypic antibodies specific to estradiol were associated with hOGG1 gene polymorphisms in BCP. IgA1-E2 and IgG2-E2 immunoanalysis may be used in BCP I stage for tumor proliferation prediction.